Microfluidics chip for directional solvent extraction desalination of seawater - Abdulbari, Hayder A.; Basheer, Esmail Abdullah Mohammed (Nature Publishing Group, 2019)
Directional solvent extraction is one of the promising membrane-less seawater desalination method. This technique was not extensively investigated due the poor mixing and separation performances of its bench-scale system. It is believed that, overcoming these drawbacks is possible now with the rapid development of microfluidics technology that enabled high-precession micro mixing and separation. This work presents microfluidics chip for extracting and separating salt from seawater. The chip was designed with two sections for extraction and separation. In both sections, the liquids were separated using capillary channels perpendicular to the main stream. The main channels were designed to be 400 µm in width and 100 µm in height. Two streams inlets were introduced through a Y-junction containing octanoic acid as the organic phase and saltwater as the aqueous phase. The desalination performance was investigated at four different temperatures and five different solvent flow rates. Water product salinity was recorded to be as low as 0.056% (w/w) at 60 °C and 40 mL/h. A maximum water yield of 5.2% was achieved at 65 °C and 40 mL/h with a very low solvent residual (70 ppm). The chip mass transfer efficiency was recorded to be as high as 68% under similar conditions. The fabricated microfluidic desalination system showed a significant improvement in terms of water yield and separation efficiency over the conventional macroscale. The high performance of this microsystem resulted from its ability to achieve a high mixing efficiency and separate phases selectively and that will provide a good platform in the near future to develop small desalination kits for personal use.